Effects of cyclic heat treatment and aging on superelasticity in oligocrystalline Fe-Mn-Al-Ni shape memory alloy wires. (June 2017) - Ozcan, H.; Ma, Ji; Wang, S.J.; Karaman, I.; Chumlyakov, Y.; Brown, J.; Noebe, R.D.
Abstract: The effects of nano-precipitation on stress-induced martensitic transformation (SIM) in Fe43.5 Mn34 Al15 Ni7.5 shape memory alloy wires were investigated. It was shown that a large grain size to wire diameter ratio, i.e. an oligocrystalline structure, is necessary to obtain superelasticity. The critical stress for SIM and tensile strength at room temperature increase with aging time at 200 °C without loss of superelasticity. A superelastic strain of 6.7%, with tunable transformation stress level as high as 600 MPa, and a low stress hysteresis, was obtained in the aged wires. Graphical abstract: